2012
DOI: 10.1063/1.3692609
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and relaxation properties of xylitol-water mixtures

Abstract: We present the first broadband dielectric spectroscopy (BDS) and differential scanning calorimetry study of supercooled xylitol-water mixtures in the whole concentration range and in wide frequency (10(-2)-10(6) Hz) and temperature (120-365 K) ranges. The calorimetric glass transition, T(g), decreases from 247 K for pure xylitol to about 181 K at a water concentration of approximately 37 wt. %. At water concentrations in the range 29-35 wt. % a plentiful calorimetric behaviour is observed. In addition to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 54 publications
(98 reference statements)
1
23
0
2
Order By: Relevance
“…This implies that the local β-relaxation of PG becomes coupled to the water relaxation. For solutions of low water content, where more or less single water molecules are interacting with solute molecules, a previous study 25 has indicated an opposite scenario with water molecules strongly affected by the β-relaxation of the solute molecules. Therefore, for the major part of the water concentration range we should expect to see a "combined" relaxation process, containing both the main w-relaxation of water and the β-relaxation of PG or PGME.…”
Section: Resultsmentioning
confidence: 96%
“…This implies that the local β-relaxation of PG becomes coupled to the water relaxation. For solutions of low water content, where more or less single water molecules are interacting with solute molecules, a previous study 25 has indicated an opposite scenario with water molecules strongly affected by the β-relaxation of the solute molecules. Therefore, for the major part of the water concentration range we should expect to see a "combined" relaxation process, containing both the main w-relaxation of water and the β-relaxation of PG or PGME.…”
Section: Resultsmentioning
confidence: 96%
“…An understanding of this relationship would lead to considerable predictive power. Dielectric spectroscopy is an emerging technique that reveals information about molecular movement during crystallization from the amorphous state, [95,96] whereas spectroscopic methods with soft X-rays, such as XPS and NEXAFS, have been shown to be sensitive to bond lengths, coordination numbers, and the geometric arrangement of coordinating species, as well as the oxidation and charge state of solute species. and computation), polymorph [104] sulfonamides (acetone) NMR yes [79] BZP/DPA cocrystal (methanol, toluene) NMR yes [91] a-inosine (water) NMR yes [80] inosine dehydrate (water) NMR no [80] (R,S)-mandelic acid (nitromethane, acetonitrile) FTIR no [81] benzoic acid (methanol) neutron scattering no [93] 3-azabicyclo-[3.3.1]nonane-2,4-dione FTIR yes, monomers in solution, catemer in the solid.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
“…There are good grounds for the use of both neutron and light scattering together with cryo-electron microscopy to explore further the existence of prenucleation clusters in concentrated solutions of organic molecules-the existing reports for citric acid, pacetanisidide and d,l-alanine suggest that this area may be fruitful territory. Dielectric spectroscopy is an emerging technique that reveals information about molecular movement during crystallization from the amorphous state, [95,96] whereas spectroscopic methods with soft X-rays, such as XPS and NEXAFS, have been shown to be sensitive to bond lengths, coordination numbers, and the geometric arrangement of coordinating species, as well as the oxidation and charge state of solute species. XPS studies of core-level binding energies associated with hydrogen bonding and protonation have already been carried out [72][73][74][75][76][77][78]97] and together with previous studies of core-level shifts caused by van der Waals and dipole interactions [98][99][100] have prepared the ground for more detailed structural studies of solute-solvent interactions, self-association, and cluster formation.…”
Section: Challenges For Future Researchmentioning
confidence: 99%
“…Es gibt eine gute Grundlage für den Einsatz von Neutronenstreuung und Lichtstreuung zusammen mit Kryo‐Elektronenmikroskopie, um die Existenz von Keimvorläufer‐Clustern in konzentrierten Lösungen organischer Moleküle weiter zu untersuchen – die bereits vorliegenden Ergebnisse für Citronensäure, p ‐Acetanisidid und d,l ‐Alanin weisen auf ein fruchtbares Gebiet hin. Dielektrische Spektroskopie ist ein neues Verfahren, um Informationen über die Molekülbewegung während der Kristallisation aus dem amorphen Zustand zu gewinnen,95, 96 während Spektroskopie mit weichen Röntgenstrahlen, beispielsweise XPS und NEXAFS, empfindlich für Bindungsabstände, Koordinationszahlen und die geometrische Anordnung von koordinierenden Spezies ist, ebenso wie für den Oxidations‐ und Ladungszustand der gelösten Spezies. XPS‐Untersuchungen von Rumpfelektronen‐Bindungsenergien in Verbindung mit Wasserstoffbrücken und Protonierung7278, 97 und früheren Untersuchungen von Verschiebungen der Rumpfelektronen‐Energieniveaus durch Van‐der‐Waals‐ und Dipol‐Wechselwirkungen98100 bilden die Grundlage für ausführlichere Strukturuntersuchungen von Wechselwirkungen zwischen gelöstem Stoff und Lösungsmittel, Selbstorganisation und Clusterentstehung.…”
Section: Forschungsaufgaben Für Die Zukunftunclassified